The agriculture competitiveness project = (The World Bank in VietNam (WB), 2008)
The development objective of Agriculture Competitiveness Project for Vietnam is to strengthen the competitiveness of smallholder farmers, with a focus on eight provinces in central Vietnam, in collaboration with the agri-business sector. There are four components to the project. The first component of the project is enhancement of agricultural technology. This component will support the identification and implementation of applied research and the dissemination of proven technologies that are cost-efficient, responsive to market demands and incentives, and enhance the environmental sustainability of increasingly competitive farming practices. There are three subcomponents: (i) conducting technology research and development (R&D) for a competitive agriculture; (ii) enhancing sustainable farming practices; and (iii) monitoring and controlling chemical residues. The second component of the project is support to productive partnerships. This component will demonstrate the feasibility of fostering the competitiveness of small-holder farmers and agribusinesses by facilitating the establishment, development, and operation of private, demand-driven productive partnerships (through public support provided on the basis of competitive and transparent procedures), improving private service delivery supporting productive partnerships, and enhancing the provincial rural investment climate. There are three subcomponents: (i) establishing new productive partnerships; (ii) scaling up successful value chain initiatives; and (iii) implementing an information campaign, networking, and match-making. The third component of the project is provision of critical infrastructure. This component will support critical public infrastructure needs supporting the competitiveness of the agricultural sector. These investments will contribute to increased agricultural productivity and the reduction of marketing costs. There are two subcomponents: (i) supporting locally-identified infrastructure priorities; and (ii) providing infrastructure support to productive partnerships. The fourth component of the project is support for project management and institutional strengthening. This component will provide the required resources to allow for an effective management of the project and to strengthen institutional capacity in key areas, particularly at provincial, district and community level, to monitor and evaluate project activities and to sustain project interventions. There are two subcomponents: (i) supporting project management and institutional strengthening; and (ii) monitoring and evaluation.